LOST IN TRANSLATION: PROBLEMS IN TRANSLATING INDONESIAN AND ENGLISH EXPRESSIONS INTO GERMAN - Deddy Kurniawan; Rosyidah Rosyidah (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2013)
In translation, an equivalent communicative effect will be more difficult to attain, as the cultural distance between the receivers of the source and target text is greater. This may lead into what is termed as a problem of untranslatability. Cultural distance between the receivers of the source and the target text can cause some problems in translating. Sometimes is necessary to omit some features having a little or no textual relevance in a given source text. It means sacrificing less relevant textual details and maintaining more relevant ones to attain a maximum equivalent communicative effect. The paper discusses some issues related to the problems in translation, especially the phenomena that appear in the German translation from Indonesian and English expressions. Keywords: problem in translation, Indonesian translation, German translation